ISRAEL'S POLICY IN THE CONTEXT OF RUSSIA'S WAR AGAINST UKRAINE: A YEAR OF NEUTRAL AID - РОГУЛЯ, Карина (Київський національний університет імені Т. Шевченка, 2024)
Abstract. Ukrainian-Israeli relations have undergone significant structural changes since the start of the full-scale russian invasion of Ukraine on February 24, 2022. The positive pre-war dynamic of the bilateral agenda has been replaced by neutral words of support from the Israeli government and practical aloofness from the war. During the year and a half of armed aggression of the russian ederation, the government in Israel changed for three times, but each of them maintained a neutral position regarding russia's war against Ukraine, albeit with certain differences. This article is an attempt to analyze the policy of the three prime ministers of Israel - Naftali Bennett, Yair Lapid and Benjamin Netanyahu - in relation to Ukraine, as well as to evaluate the geopolitical environment in the Middle East, which is the main factor behind the passivity of the State of Israel in the context of providing assistance to Ukraine. The main focus is on the public reaction, practical steps and reservations of the Israeli government regarding support for Ukraine. The political activity of each prime minister, the internal environment and national interests of the State of Israel from the point of view of decision-making in favor of Ukraine were evaluated. The geopolitical reasons for Israeli neutrality in relation to the russian war against Ukraine are analyzed.

Анотація. Українсько-ізраїльські відносини зазнали значних структурних змін після початку повномасштабного вторгнення росії в Україну 24 лютого 2022 року. Довоєнна позитивна динаміка двостороннього порядку денного змінилася нейтральними словами підтримки з боку ізраїльського уряду та практичною відстороненістю від війни. За півтора роки збройної агресії рф уряд в Ізраїлі змінювався тричі, однак нейтральну позицію щодо війни росії проти України зберігав кожен із них, хоч і з певними відмінностями. Ця стаття є спробою проаналізувати політику трьох прем’єр-міністрів Ізраїлю – Нафталі Беннетта, Яїра Лапіда та Беньяміна Нетаньягу – стосовно України, а також дати оцінку геополітичному середовищу на Близькому Сході, що є основним чинником пасивності Держави Ізраїль у контексті надання допомоги Україні. Основну увагу зосереджено на публічній реакції, практичних кроках та застереженнях ізраїльського уряду щодо підтримки України. Оцінено політичну діяльність кожного прем’єр-міністра, внутрішнє середовище та національні інтереси Держави Ізраїль з погляду ухвалення рішень на користь України. Проаналізовано геополітичні причини ізраїльського нейтралітету стосовно російсько-української війни.
ПОЛІТИКА ІЗРАЇЛЮ В КОНТЕКСТІ ВІЙНИ РОСІЇ ПРОТИ УКРАЇНИ: РІК НЕЙТРАЛЬНОЇ ДОПОМОГИ
Keywords: Israeli-Ukrainian relations; full-scale war of russia against Ukraine; Middle Eastern neutrality; geopolitical interests; red lines.; international relations; Middle East; Ukrainian-Israeli relations; regional security; ізраїльсько-українські відносини повномасштабна війна росії проти України; близькосхідний нейтралітет; геополітичні інтереси; червоні лінії.; міжнародні відносини; Близький Схід; українсько-ізраїльські відносини; регіональна безпека